DESIGN AND EVALUATION OF FLUTAMIDE-LOADED POLYCAPROLACTONE NANOPARTICLES BY 23 FACTORIAL DESIGN AND NANOPRECIPITATION METHOD - S, Venkateswara Rao (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present work was aimed to prepare and evaluate polymeric nanoparticles (NPs) of flutamide by nanoprecipitation method and factorial. The influences of various formulation components such as polymer, organic phase volume, and surfactant on the characteristics of NPs were investigated. Methods: The polycaprolactone (PCL) loaded with drug was evaluated for surface morphology, surface charge, particles size, encapsulation efficiency, drug content, and in vitro release studies. Fourier transform infrared studies were indicated no interaction between the drug and polymer. Results: The results of the drug release study of NPs may fit with different kinetic equations. The particle size varied from 128 to 317 nm and zeta potential was in negative and its value found to be - 46.4 mv. The content of flutamide was found in between 74%±0.72 to 92%±0.53 in flutamide loaded PCL NPs. The minimum and maximum entrapment efficiencies were found to be of 75%±0.66 and 92%±0.70. The percentage yields of all formulations were in the range of 46.05%±1.56–86.78%±1.32. The in vitro drug release followed zero order with sustained behavior for a period of 24 h. Results of accelerated storage conditions of optimized formulation revealed that no significant changes in formulation F2. Conclusion: The present investigation opens new frontiers in developing flutamide NPs for targeting delivery to the prostate for the prostate cancer treatment which also overcome the problems associated with conventional formulations such as multiple-dose therapy, poor patient compliance, and high treatment cost.